ANALISIS KESULITAN MENYIMAK SISWA KELAS II DALAM PEMBELAJARAN BERBASIS VIDEO CERITA PENDEK - Sandy Dwi Febrianto; Fulusia Nurmawati; Anna Mariyani (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Listening learning in elementary schools requires media that can help students understand information in a more concrete and engaging way. Short story videos are one of the media used in Indonesian language learning at elementary schools. In practice, some students were found to experience difficulties in understanding the story content after listening activities. This study aims to analyze the forms of listening difficulties experienced by second grade students of SDN 1 Botoreco in short story video-based learning, the factors causing these difficulties, and the teacher’s strategies to overcome them. This study employed a qualitative approach with a descriptive method. Data were obtained through observation, semi-structured interviews, questionnaires, and documentation. The research subjects included second grade teachers and students of SDN 1 Botoreco. Data analysis used the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The findings showed that students experienced difficulties in understanding the storyline, maintaining focus during listening activities, and comprehending certain vocabulary used in the video. These difficulties were influenced by the characteristics of lower grade students, language use in the video, video duration, and differences in students’ cognitive abilities. The use of short story videos was able to increase students’ learning interest when accompanied by active teacher involvement in guiding the listening process. Therefore, audiovisual-based listening learning needs to be designed to support the optimal development of elementary school students’ literacy skills. ABSTRAK Pembelajaran menyimak di sekolah dasar memerlukan media yang mampu membantu siswa memahami informasi secara lebih konkret dan menarik. Video cerita pendek menjadi salah satu media dalam pembelajaran Bahasa Indonesia di sekolah dasar. Praktiknya, ditemukan siswa mengalami kesulitan memahami isi cerita setelah kegiatan menyimak. Tujuan penelitian ini untuk menganalisis bentuk kesulitan menyimak siswa kelas II SDN 1 Botoreco dalam pembelajaran berbasis video cerita pendek, faktor penyebabnya, serta strategi guru dalam mengatasinya. Pendekatan kualitatif dengan metode deskriptif digunakan dalam penelitian ini. Data diperoleh dari observasi, wawancara semi terstruktur, angket, dan dokumentasi. Subjek penelitian memcakup guru kelas II dan siswa SDN 1 Botoreco. Analisis data menggunakan model Miles dan Huberman melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan siswa mengalami kesulitan memahami alur cerita, mempertahankan fokus saat menyimak, serta memahami kosakata tertentu dalam video. Kesulitan dipengaruhi oleh karakteristik siswa kelas rendah, penggunaan bahasa dalam video, durasi tayangan, dan perbedaan kemampuan kognitif siswa. Penggunaan video cerita pendek mampu meningkatkan minat belajar siswa apabila disertai keterlibatan aktif guru dalam membimbing proses menyimak. Pembelajaran menyimak berbasis audiovisual perlu dirancang agar membantu perkembangan kemampuan literasi siswa sekolah dasar secara optimal.